2019
DOI: 10.5005/jp-journals-10024-2616
|View full text |Cite
|
Sign up to set email alerts
|

Role of Synthetic Hydroxyapatite—In Socket Preservation: A Systematic Review and Meta-analysis

Abstract: Since a long time, the preservation of the socket is emphasized for various reasons. Many studies have suggested the ridge preservation through socket grafting using various bone graft substitute materials (GSMs). But none of the studies suggested the material of choice for the grafting. So, the systematic review was planned to analyze the outcomes of synthetic hydroxyapatite (SHA) graft material for socket preservation. The review was aimed to determine the existing evidence for the use of SHA GSM for graftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…HAp is a material that shows a slow resorption in the biological environment [32], which according to some authors may represent a greater susceptibility to infections [33]. In our study, although we encountered residual particles of HAp in all samples, no signs of local infection were identified.…”
Section:  Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…HAp is a material that shows a slow resorption in the biological environment [32], which according to some authors may represent a greater susceptibility to infections [33]. In our study, although we encountered residual particles of HAp in all samples, no signs of local infection were identified.…”
Section:  Discussionsupporting
confidence: 43%
“…Although initially it was believed that osteoinduction is determined only by the concentration of bone growth factors in the circulating blood [ 30 ], more recent research has shown that the geometric structure of HAp and its microporosity also may determine the transformation of stem cells into osteoblasts [ 31 ]. HAp is a material that shows a slow resorption in the biological environment [ 32 ], which according to some authors may represent a greater susceptibility to infections [ 33 ]. In our study, although we encountered residual particles of HAp in all samples, no signs of local infection were identified.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 19 20 21 22 23 ] that cannot be standardized to provide conclusive remarks. [ 11 ] As a result, this review focused on the specific review question on the use of the biphasic calcium phosphate for socket preservation over xenografts and other alloplastic materials.…”
Section: Discussionmentioning
confidence: 99%
“…As have documented that the nature, physio-chemical properties have profound effect in the bone regeneration. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation